Guillain‐Barré Syndrome During Platinum‐Based Chemotherapy: A Case Series and Review of the Literature. (15th October 2019) - Pappa, Evangelia; Berzero, Giulia; Herlin, Bastien; Ricard, Damien; Tafani, Camille; Devic, Perrine; Maillet, Denis; Borden, Alaina; Viala, Karine; Maisonobe, Thierry; Lenglet, Timothée; Weiss, Nicolas; et al.
Abstract: : Platinum‐based chemotherapy is commonly associated with toxic sensory neuropathies, but also, although rarely, with Guillain‐Barré syndrome (GBS). We describe five patients who developed GBS while receiving platinum‐based chemotherapy for a solid tumor and report the five cases published so far. Most patients had received cumulative platinum doses below known neurotoxic levels, and all of them had an optimal outcome after platinum discontinuation, associated in most cases with administration of intravenous immunoglobulin. Clinical presentation, electroneuromyography, and cerebrospinal fluid analysis help clinicians to differentiate GBS from toxic neuropathy. Platinum compounds are the only chemotherapeutic agents used for solid tumors that have been associated to GBS. Thus, we propose that GBS may constitute a non–dose‐dependent side effect of platinum drugs and that awareness needs to be raised among oncologists on this rare but potentially life‐threatening complication of platinum chemotherapy. Abstract : To increase awareness of a potentially life‐threatening complication of platinum chemotherapy, this brief communication describes five patients who developed GBS while receiving platinum‐based chemotherapy for a solid tumor and reports the results of a review of the literature on this topic.